Perencanaan Penerangan Jalan Umum (PJU) Menggunakan Energi Baru dan Terbarukan di Desa Tanjung Gusta, Dusun III, Kecamatan Sunggal - Ilyasa Ramadhan; Rahmaniar; Erpandi Dalimunthe (CV. Hawari, 2025)
Indonesia has great potential in renewable energy, especially solar energy, due to its geographical location in the tropics. This study aims to plan an efficient and sustainable Street Lighting (PJU) system in Tanjung Gusta Village, Sunggal District, by utilizing new and renewable energy (EBT). Tanjung Gusta Village has a need for adequate street lighting to improve safety, mobility, and quality of life for the community. The research method includes a field survey to analyze conditions, calculation of lighting needs based on applicable standards, and design of a PJU system using EBT. The results of the study indicate that a PJU system with solar power is the most suitable solution for Tanjung Gusta Village, considering the availability of resources. The planning of this solar PJU system includes selecting the type of lamp to be used, determining the capacity of solar panels and batteries, and calculating the optimal layout and height of lamp posts.